What constrains people's ability to learn about the testing effect through task experience?. Issue 10 (26th November 2022) - Rivers, Michelle L.; Dunlosky, John; McLeod, Mason
ABSTRACT: What constrains people's ability to learn from experience about the effectiveness of practice testing versus restudying for memory (i.e., the testing effect)? Across two cycles, participants studied word pairs, practiced each pair through either restudying or testing, predicted how many pairs they would recall for each strategy, then completed a critical test on the pairs. During this test, participants either received feedback about the number of pairs they had correctly recalled or made postdictions about their performance for each strategy (i.e., generated their own feedback). During both cycles, participants predicted they would recall an equivalent number of tested and restudied pairs, although they actually recalled more tested pairs. However, when participants experienced a larger testing effect, they estimated recall performance more accurately for each strategy and updated their knowledge about the testing effect. Thus, peoples' ability to learn from experience about the testing effect is primarily constrained not by a failure to initiate the metacognitive processes required to monitor and track recall performance by strategy, but by the metacognitive burden of discriminating between small differences in recall between tested versus restudied material. In summary, people can learn from experience about the testing effect when the metacognitive burden is lifted.